Manifestation of Surrealism in Charlotte Perkins Gilman’s Short Story The Yellow Wallpaper - Muhajir, Fatimah; Nugroho, Bayu Aji (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
ABSTRACT This study examines the elements of surrealism in literary works, focusing on how authors employ realist techniques to explore subconscious realities and create complex meanings. The research uses a descriptive-qualitative method by describing data such as dialogues, narratives, or quotations, which are then processed through elaboration and analysis. This study applies surrealist literary theory, primarily referring to the ideas of André Breton as a central figure in the surrealist movement, combined with Sigmund Freud’s psychological theory. The object of analysis is a short story titled